Combination of Photodynamic Therapy and Oral Antifungals for the Treatment of Onychomycosis - Alba Navarro-Bielsa; Tamara Gracia-Cazaña; Pilar Robres; Concepción Lopez; María Dolores Calvo-Priego; Carmen Aspiroz; Yolanda Gilaberte (Pharmaceuticals, 2022)
Onychomycosis accounts for 50% of nail disorders, making it one of the most prevalent fungal diseases and a therapeutic challenge. Photodynamic therapy (PDT) could constitute a therapeutic alternative, owing to its good adherence, the low probability of resistance, the lack of interaction with antimicrobials, and its favorable adverse effect profile. This retrospective observational study included all patients with a microbiological diagnosis of onychomycosis treated with PDT at Miguel Servet University Hospital, Zaragoza (Spain), between January 2013 and June 2021. The protocol consisted of pre-treatment with 40% urea for 7 days, followed by 16% methyl-aminolevulinate (MAL) for 3 h and subsequent irradiation with a red-light LED lamp (37 J/cm2), every 1 or 2 weeks. Combined treatment with oral and/or topical antifungals was recorded. Of the 20 patients included (mean age, 59 ± 17 years), 55% were men. The most frequently detected microorganism was Trichophyton rubrum (55%). The most commonly affected location was the feet (90%): 50% of these cases were associated with tinea pedis. The median (standard deviation) number of PDT sessions was 6 (2.8). PDT was combined with systemic terbinafine (250 mg/day) in 10 cases (in 8 cases, this was administered for only 1 month), and with topical terbinafine in 3 cases. A complete clinical response was achieved in 80% (16) of cases and microbiological cure in 60% (12). PDT is a therapeutic alternative for onychomycosis, and can be administered either in monotherapy or combined with antifungals, allowing for a reduction in the duration and possible adverse effects of antifungal treatment and achieving higher cure rates than those obtained with either treatment alone.